Geodetic Evidence of Shallow Slow‐Slip Phenomena Beneath the Southern Ryukyu Forearc - Chi‐Hsien Tang; Ya‐Ju Hsu; Yutaro Okada; Yusaku Ohta; Takeshi Sagiya; Pei‐Ru Jian; Yoshiaki Tamura; Takaaki Jike (Geophysical Research Letters)
Abstract While slow slip events (SSEs) are recognized as a ubiquitous phenomenon in subduction zones, accurately tracking the spatiotemporal distribution of shallow SSEs remains challenging. Here, we investigate the potential occurrence of shallow SSEs in the southern Ryukyu forearc at the western boundary of the Philippine Sea plate using 25 years of Global Navigation Satellite System data. We identify trenchward transient motions near the Miyako Islands, with cumulative displacements of ∼10 mm between 2009 and 2011, indicating shallow SSEs that released a geodetic moment equivalent to Mw 6.8. These SSEs likely occurred updip of a Mw 6.1 interplate earthquake, whose associated positive Coulomb stress changes may have encouraged slow slip. Our results indicate that the shallow southern Ryukyu plate interface can accumulate elastic strain and release energy either aseismically or seismically. We therefore emphasize the importance of near‐trench seafloor geodesy to fully characterize fault slip behaviors beneath the southern Ryukyu forearc.